The Use of Guessing Meaning from Context in Improving Students’ Vocabulary Mastery - Rihadhatul Nur Ramadhiani; Andi Patmasari; Abd. Kamaruddin; Nadrun Nadrun (Journal of English Language and Education, 2026)
Vocabulary mastery is a fundamental aspect of language learning as it supports students’ ability to understand and use language effectively. However, many students still experience difficulties due to limited vocabulary knowledge and the use of less effective teaching strategies in the classroom. This study aims to investigate the effectiveness of guessing meaning from context in improving students’ vocabulary mastery. This research employed a quasi-experimental design involving an experimental group and a control group consisting of 49 eighth-grade students at SMPN 1 Mepanga. The data were collected through test (pre-test and post-test) used to measure students’ vocabulary achievement. The results showed that the experimental group outperformed the control group. The t-test result revealed that t-count (4.54) was higher than t-table (2.01) at the 0.05 significance level, indicating that the atlernative hypothesis was accepted. Therefore, guessing meaning from context is an effective strategy for improving students’ vocabulary mastery.